Diagnosing and treating mental illness - Lundy, Allan (New York Chelsea House, 1990)
Discusses the types of mental illness and describes how they are diagnosed and treated.
Keywords: Mental illness -- Juvenile literature; Mental illness; Psychiatry -- Juvenile literature; Psychiatry; Psychotherapy -- Juvenile literature; Psychotherapy